Synthesizing and characterization of Lead Halide Perovskite Nanocrystals solar cells from reused car batteries - Aziz, Issa M; Salih, Raad N; Jaqsi, Mohammed K (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
With the rapid increase of efficiency up to 23.7% during the past few years, hybrid organic-inorganic metal halide perovskite solar cells (PSCs) have become a research “hot spot” for many solar cell researchers. The perovskite materials show various advantages due to unique characteristics of perovskite materials, such as high photo-to-electric conversion efficiency, direct band gap, high light absorption coefficient, high charge-carrier mobility and long electron-hole electron transport distance. The low-cost fabrication techniques together with the high efficiency makes PSCs comparable with Si-based solar cells. This paper begins with the discussion of crystal structures of perovskite based on recent research findings. The following part of this paper discussion of synthetic process of lead iodide perovskite materials from lead-acid battery and Harvesting material from the anodes and cathodes of car battery; synthesizing PbI2 from the collected materials and compare with pure Lead iodide to know the absolute by XRD peak, depositing lead iodide perovskite nanocrystals. Efficient flexible PSCs are fabricated onto FTO glass substrate by a two-step coating method under ambient condition. By adjusting the concentration of precursor CH3NH3I (MAI), the morphology and thickness of perovskite layer is effectively tailored, according to SEM analysis and using TiO2 as electron transport layer instead of ZnO and CuI instead of spiro-OMeTAD as hole transport layer.